2014
DOI: 10.1021/cs501371q
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Depolymerization into Aromatic Monomers over Solid Acid Catalysts

Abstract: It is imperative to develop an efficient and environmentally benign pathway to valorize profusely available lignin, a component of non-edible lignocellulosic materials into value-added aromatic monomers, which can be used as fuel additives and platform chemicals. To convert lignin, earlier studies used mineral bases (NaOH, CsOH) or supported metal catalysts (Pt, Ru, Pd, Ni on C, SiO 2 , Al 2 O 3 etc.) under hydrogen atmosphere but these methods face several drawbacks such as corrosion, difficulty in catalyst r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
200
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(212 citation statements)
references
References 81 publications
(230 reference statements)
9
200
1
2
Order By: Relevance
“…In Deepa's report (Deepa and Dhepe, 2015), lignin conversion generated wide range of products from 10 to 25 min. However, in this work, only seven products were detected by GC-MS, indicating much higher selectivity of this catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Deepa's report (Deepa and Dhepe, 2015), lignin conversion generated wide range of products from 10 to 25 min. However, in this work, only seven products were detected by GC-MS, indicating much higher selectivity of this catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Among various catalysts for lignin depolymerization, zeolites are widely accepted due to their low-cost, high surface area, and outstanding acid sites catalytic performance (Taarning et al, 2011;Ben and Ragauskas, 2012;Wang et al, 2017). External Brønsted acidity in meso-/microporous zeolites was reported to effectively affect the selectivity of de-alkylation and de-etherification reactions in parallel during lignin conversion (Taarning et al, 2011;Singh and Ekhe, 2014;Deepa and Dhepe, 2015). Deepa reported that aromatic monomers were the predominant products using zeolite as solid acid catalysts for lignin depolymerization at 250°C in H2O/CH3OH mixture (Deepa and Dhepe, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 As a natural amorphous three-dimensional polymer consisting mainly of methoxylated phenylpropane units, 2,5 lignin is linked to other main components, such as cellulose and hemicellulose, in a variety of ways, including hydrogen, ester, and covalent bonds. 6 Depolymerization of lignin is the key step towards making lignin cost-effective as a raw material, 7 but its highly random and branched three-dimensional polyphenolic structure leads to its resistance to depolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the available lignin is usually burned for providing the heat (Chapple et al, 2007) that does not satisfy the need for effective power generation. Different ways of lignin recycling by using catalysts and ionic liquids are reflected in numerous publications (Deepa & Dhepe, 2015., Nanayakkara et al, 2014 however these approaches are often expensive and do not meet the requirements for sustainable lignin recycling. One of the environmentally friendly approaches is to use naturally existing enzymes that are capable of degrading lignin and biomass (Christopher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%